Pensar América Latina desde la “Tierra nuestra” (2022)
This article presents a bibliographic review of the novel Terra nostra by Carlos Fuentes, and brings about dialogues that show its relevance and its interdisciplinary relationship with philosophy, history, art, society and culture. The structural criteria distinguish these topics: (1) myth and identity, (2) relationships with the other, (3) image and memory, and (4) the reconstruction of what we are and will be. Time spans of eight years were taken into account, from the time of its publication, 1975, to the year 2015. The studies highlight the problems of Latin American identity, intertextuality, multiculturalism, and conquest; they reveal their relevance in the 21st century through miscegenation, the cultural traditions of the Old and the New World, and the other worlds; and they express the need to rebuild a new humanism.